From the dust - Sempangi, F. Kepa; Melvin, Jennifer (The Lutterworth Press, 2008)
She was dirty and dusty. Her curly hair had seen neither a comb nor water for months. In one hand she carried a package of cigarettes and in the other a solvent rag.' Young Namusisi had no home, no family, no money for school fees, and no one to love her or care for her. She survived in the culture of the 'buyaye' on the streets, parking lots, and porches of the city of Kampala, Uganda. But one day she met Daddy Kefa and her life was changed. He took her to his children's home where she was provided for and was shown the love of Christ. Namusisi was just one of more than 6,000 Ugandan street c.